2018
DOI: 10.1016/j.cmi.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of HIV infection and of asymptomatic sexually transmitted infections among men who have sex with men

Abstract: The implementation of the Check-Ear Project in a MSM community centre allowed for the identification of early HIV infections and asymptomatic STI among MSM. The high incidence of HIV infections and the high prevalence of STI strongly support the recommendation of periodic screenings among sexually active MSM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
4
6
0
Order By: Relevance
“…As in the report from the Centre for Disease Prevention and Control [13], and in line with other studies, 78.4% of our respondents had been tested for HIV [14]young (median age 29 [interquartile range 23-35], and the likelihood of having been tested was higher in the group that had experienced STIs. The rate of HIV infection in our sample was consistent with that of a recent study in which the prevalence of HIV among MSM was 3.9% [15]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As in the report from the Centre for Disease Prevention and Control [13], and in line with other studies, 78.4% of our respondents had been tested for HIV [14]young (median age 29 [interquartile range 23-35], and the likelihood of having been tested was higher in the group that had experienced STIs. The rate of HIV infection in our sample was consistent with that of a recent study in which the prevalence of HIV among MSM was 3.9% [15]. …”
Section: Discussionsupporting
confidence: 90%
“…Several studies have revealed an association between substance use and sexual risk-taking, especially among MSM [15]. The use of alcohol and illicit drugs is sometimes a part of this community’s socializing behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The present results confirmed the high risk for acquisition of HIV infection among MSM selected for high-risk behaviour in a middle-income country, a result similar to that found in a highincome country [3]. Consequently, these results stress the need for screening programmes for the early detection of HIV among high-risk MSM.…”
supporting
confidence: 89%
“…Our group has recently published a high incidence of HIV among MSM at high risk for HIV infection in a high-income country (Spain) [3]. In parallel, a second comparable cohort in a middle-income country (Peru) assessed the early diagnosis of HIV infections (during at least 2 years of follow-up) in HIV-uninfected MSM at high risk of HIV infection.…”
mentioning
confidence: 99%
“…Most HIV-1-negative controls were enrolled from a prospective cohort of HIV-negative MSM who attend quarterly medical and counseling visits at a community-based center in Barcelona. 44,45 Microbial gene richness Microbial gene richness values obtained by whole fecal metagenome shotgun sequencing followed a bimodal distribution across the study cohort ( Fig. 1a).…”
Section: Study Subjectsmentioning
confidence: 97%